Macroeconomic effects of capital tax rate changes - Saroj Bhattarai; Jae Won Lee; Woong Yong Park; Choongryul Yang (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study aggregate, distributional, and welfare effects of a permanent reduction in the capital tax rate in a dynamic equilibrium model with capital-skill complementarity. Such a tax reform leads to expansionary long-run aggregate effects, but is coupled with an increase in the skill premium. Moreover, the expansionary long-run aggregate effects are smaller when distortionary labor or consumption tax rates have to increase to finance the capital tax rate cut. An extension to a model with heterogeneous households shows that consumption inequality increases in the long-run. We study transition dynamics and show that short-run effects depend critically on the monetary policy response: whether the central bank allows inflation to directly facilitate government debt stabilization and how inertially it raises interest rates. Finally, we contrast the long-term aggregate welfare gains with short-term losses, as well as in the model with heterogeneous households, show that welfare gains for the skilled go together with welfare losses for the unskilled.
Keywords: E62; E63; E52; E58; E31; 330; capital tax rate; permanent change in the tax rate; capital-skill complementarity; skill premium; inequality; transition dynamics; monetary policy response